Factors affecting access to healthcare for young people in the informal sector in developing countries: a systematic review - Oladosu, Ayomide Oluwaseyi; Khai, Tual Sawn; Asaduzzaman, Muhammad (Frontiers in Public Health, 2023)
Background: Young people are increasingly seeking employment in the informal sector due to increasing global unemployment. However, the precarious nature of work in the informal sectors, coupled with the high risk of occupational hazards, calls for a greater need for effective healthcare for informal sector workers, particularly young people. In addressing the health vulnerabilities of informal workers, systematic data on the determinants of health is a persistent challenge. Therefore, the objective of this systematic review was to identify and summarize the existing factors that affect access to healthcare among young people from the informal sector. Methods: We searched six data databases (PubMed, Web of Science, Scopus, ProQuest, Crossref, and Google Scholar), which was followed by hand searching. Then we screened the identified literature using review-specific inclusion/exclusion criteria, extracted data from the included studies and assessed study quality. Then we presented the results in narrative form, though meta-analysis was not possible due to heterogeneity in the study design. Results: After the screening, we retrieved 14 studies. The majority were cross-sectional surveys and were conducted in Asia (n = 9); four were conducted in Africa, one each in Europe and South America. Samples ranged in size from 120 to 2,726. The synthesized results demonstrate that problems of affordability, availability, accessibility, and acceptability of healthcare were barriers to young informal workers seeking healthcare. We found social networks and health insurance as facilitators of access for this group of people. Conclusions: To date, this is the most comprehensive review of the evidence on access to healthcare for young people in the informal sector. Our study finding highlights the key gaps in knowledge where future research could further illuminate the mechanisms through which social networks and the determinants of access to healthcare could influence the health and well-being of young people and thus inform policy development.